Effects of training at the ventilatory threshold on the Ventilatory threshold and performance in trained distance runners - Hoffmann, R. L. (The Journal of Strength and Conditioning Research, 1999)
This study compared the effects of different frequencies of training specifically at the ventilatory threshold (VT) in already trained distance runners. The purposes of the investigation were to determine if the training elicited favorable performance enhancements and, if so, to provide information regarding a more beneficial frequency of VT training. Eight trained distance runners underwent maximal testing to determine o2 peak and VT and completed a timed performance run on the treadmill. Four subjects then added three 20-minute runs per week at the velocity that elicited the VT to their training for 6 weeks (3X), while the other 4 subjects added 1 VT run per week (1X). When retested at 3 weeks, the 3X group exhibited a significant increase in VT, but after 3 additional weeks of training no further significant changes were detected. Conversely, the 1X group showed no alteration in VT after 3 weeks but showed a similar overall increase in VT as the 3X group at the conclusion of the study, despite the much lower frequency of VT training. Both groups also exhibited significant increases in o2 peak and an increase in performance of approximately 36%. It was confirmed that training at the VT is an effective method for improving middle distance running performance and that the beneficial changes observed can be achieved just as readily with VT sessions of moderate frequency.